CHILDREN’S PERSONAL READINESS FOR SCHOOL ACTIVITIES - Vacheva, Snezhana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
The paper dwells on the model of children’s personal readiness for studying in school. A number of characteristic features regarding children’s willingness are also discussed in the paper: child’s interest in school activities; his/her readiness to become a student and occupy a new position in the society; children’s personal drive for taking part in school activities; adopting studying skills; a level of social communication; a number of personal characteristic features, etc.